Language and solitude : Wittgenstein, Malinowski, and the Habsburg dilemma - Gellner, Ernest (Cambridge University Press, 2013)
Ernest Gellner (1925-1995) has been described as 'one of the last great central European polymath intellectuals'. His last book throws new light on two leading thinkers of their time. Wittgenstein, arguably the most influential and the most cited philosopher of the twentieth century, is famous for having propounded two radically different philosophical positions. Malinowski, the founder of modern British social anthropology, is usually credited with being the inventor of ethnographic fieldwork, a fundamental research method throughout the social sciences. In a highly original way, Gellner shows how the thought of both men grew from a common background of assumptions - widely shared in the Habsburg Empire of their youth - about human nature, society, and language. Tying together themes which preoccupied him throughout his working life, Gellner epitomizes his belief that philosophy -- far from 'leaving everything as it is' -- is about important historical, social and personal issues